Understanding innovative Information Systems (IS) use of frontline employees in hotels: Proactivity, psychological empowerment, self-learning, and service quality efficacy - Kyoung-Joo Lee (Global Business & Finance Review (GBFR), 2020)
Purpose: As hotels make huge investments in the information systems (IS) to improve operational efficiency and service quality, understanding the pattern of employees' IS behavior is crucial to gain a high return on the investment. Although the technology acceptance model (TAM) explained the early voluntary IS use, it has limitations to explain the variety of IS behaviors in the current mandatory context. Design/methodology/approach: Understanding the innovative information systems (IS) use as the most prominent behaviour patterns, this research proposes an integrative model to analyze the positive influence of the innovative IS behavior and to investigate its predictors. Based on a survey of 189 hotel front office employees, this study tests the research model by adopting the PLS-SEM. Findings: As a personal positive outcome of innovative IS use, this research focuses on the service quality efficacy of service providers. As a predictor at the individual and organizational level, this study shows the positive and significant influence of the proactive personality and the psychological empowerment on the innovative IS use. Furthermore, it also found the mediation effects of users' self-learning to elucidate the path of how the predictor variables lead to innovative IS applications. Research limitations/implications: This paper highlights the concept of innovative IS use and shows its importance in improving the hotel frontline employees' self-efficacy and the quality of services. Furthermore, it advises hotel management to select proactive employees, empower them, and promote self-learning activities to improve the innovative IS use. Future research will advance the literature by investigating the complex interactions of the key prediction variables. Originality/value: This research not only stresses the concept of the innovative IS behavior to improve the hotel operational efficiency and service quality, but also presents an integrative model that shows the predictors of innovative IS behavior and its impact on the hotel employees' self-confidence in their service ability.
Keywords: 650; Innovativeness; Proactivity; Psychological empowerment; Self-learning; Service quality efficacy